Performance of an environmentally‐aligned, low maintenance flood alleviation scheme on the Burn of Mosset, Forres, Scotland. (11th July 2022) - Johnson, Matthew F.; Edwards, Patrick; Todd, Rachael; Castro, Janine M.; Thorne, Colin R.
Abstract: Flooding of the town of Forres, Scotland prompted the implementation of a flood alleviation scheme (FAS) featuring a low earth‐fill dam constructed upstream of the town to create a flood retention area, limiting peak discharges entering the urban area. Flow through the dam is controlled by a weir, and it was recognised that if coarse sediment, large wood, and/or debris collected at the weir this could adversely affect its performance. To ensure reliable operation of the weir, the "Burn Management Works" (BMW) were designed to reconnect the embanked, elevated river channel to its floodplain, naturally retaining coarse sediment, large wood, and debris upstream of the dam. The FAS became operational on August 28, 2009 and impounded floodwater for the first time just 1 week later. Here, we report the results of monitoring of the BMW performed between 2011 and 2018. We find that the BMW have fulfilled their primary, flood alleviation functions by retaining large amounts of sediment and large wood without the need for maintenance. In so doing, the BMW has evolved from the single‐thread, trapezoidal, pilot channel constructed through the initially dry pasture, to the shifting mosaic of anastomosed channels, ponds, wetlands, and scrublands that now comprise the fully‐connected floodplain. In parallel, local interest groups have transformed this flood defence asset into a bird and wildlife area that is enjoyed by the community. Lessons learned from the BMW can inform other projects seeking to use nature‐based solutions to deliver sustainable flood risk management while simultaneously achieving goals for river restoration and community engagement.